India and Asean engagement in the South China sea - Sharma, Srijana (Indian Journal of Political Science)
The South China Sea draws the attention of the world player because of its complicated geo-strategic location which augmented the conflict among the claimant countries of ASEAN. China's assertiveness and its historical claim to control the disputed islands are noticeable. Numerous external powers focus on international maritime laws and specifically the reconsideration of maritime security the south China Sea. Advocates for maritime security in the South China Sea have tremendously broadened their view and influence in the maritime realm. India has revived its vision clear for major players by changing its "Look East Policy into Act East Policy". In the disputed South China Sea, India has naturally shoved strategic hesitancy and has garnered mixed reactions from amongst the claimants' countries. This assertiveness maybe due to the presence of vast resources of oil and gas reserves in region. Moreover, China's assertiveness through its nine- dash line and the claims made by the six nations is the political reason for the dispute. Nonetheless, strategic considerations, given the importance of sea route connections. This paper analysed in the context of the international political scenario and its impact on India and Southeast Asia, role and interest of ASEAN countries and India. - Reproduced
Keywords: China, India, ASEAN, South China Sea, maritime security